Multisite Validation of Cryptococcal Antigen Lateral Flow Assay and Quantification by Laser Thermal Contrast - Boulware, David R.; Rolfes, Melissa A.; Rajasingham, Radha; Hohenberg, Maximilian von; Qin, Zhenpeng; Taseera, Kabanda; Schutz, Charlotte; Kwizera, Richard; Butler, Elissa K.; Meintjes, Graeme; Muzoora, Conrad; Bischof, John C.; et al. (Emerging infectious diseases, 2014)
Cryptococcal meningitis is common in sub-Saharan Africa. Given the need for data for a rapid, point-of-care cryptococcal antigen (CRAG) lateral flow immunochromatographic assay (LFA), we assessed diagnostic performance of cerebrospinal fluid (CSF) culture, CRAG latex agglutination, India ink microscopy, and CRAG LFA for 832 HIV-infected persons with suspected meningitis during 2006–2009 (n = 299) in Uganda and during 2010–2012 (n = 533) in Uganda and South Africa. CRAG LFA had the best performance (sensitivity 99.3%, specificity 99.1%). Culture sensitivity was dependent on CSF volume (82.4% for 10 μL, 94.2% for 100 μL). CRAG latex agglutination test sensitivity (97.0%–97.8%) and specificity (85.9%– 100%) varied between manufacturers. India ink microscopy was 86% sensitive. Laser thermal contrast had 92% accuracy (R = 0.91, p<0.001) in quantifying CRAG titers from 1 LFA strip to within <1.5 dilutions of actual CRAG titers. CRAG LFA is a major advance for meningitis diagnostics in resource-limited settings.
Keywords: Cryptococcal meningitis; Cerebrospinal fluid; Cryptococcal Antigen; Lateral Flow